Pengaruh Citra Merek, Harga dan Kualitas Produk terhadap Keputusan Pembelian yang Dimediasi Minat Beli pada UMKM Warung Lesehan Yu Siti The Effect of Brand Image, Price, and Product Quality on Purchase Decisions Mediated by Purchase Intention at the MSME - Haryani, Puji; Arum, Khorifah; Akaresti, Losina (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2025)
This study aims to analyze the effect of brand image, price, and product quality on purchasing decisions, mediated by purchase intention, at the UMKM Warung Lesehan Yu Siti in Hong Kong. This quantitative research includes all consumers of Warung Lesehan Yu Siti as the study population, although the exact population size is unknown. The sample comprises 100 respondents selected through direct sampling. The results indicate that price directly influences purchasing decisions, while brand image, price, and product quality each have an effect on purchase intention. Purchase intention positively affects purchasing decisions, although brand image does not directly impact these decisions. Product quality emerges as the primary factor influenced by purchase intention, whereas brand image and price cannot be mediated by it. Product quality and price are the main considerations for consumers when making a purchase, with purchase intention serving as the primary mediator between them. These findings have implications for UMKM’s marketing strategy, suggesting that enhancing product quality and implementing a competitive pricing strategy can help increase sales.